The Importance of Prosthetic Driven Approach for Implant Placement - Jonathan Antono; Trijani Suwandi (Jurnal Kedokteran Gigi Terpadu, 2021)
Background : Nowadays implants are becoming a crucial part of modern dentistry. The old “surgically driven approach’ has now evolved to a “prosthetically driven approach”. The accuracy to locate the implant fixture is determined by careful planning, evaluation, diagnostic aids and nonetheless operator experiences’ also play a big role in achieving the best possible outcome. Case report : a 22 years old woman wants implant placement on tooth 36 and 46 to restore the mastication function. Implant placements were done with 2 stages of surgery, and due to covid-19; the second stage was executed 1 year later. The final prosthesis outcome is not as ideal as planned earlier due to mesial shifting of tooth 37 and operator was not alerted when doing so. Conclusion : Evaluation and measurement of clinical condition throughout the whole treatment phases are playing an important part for achieving the best possible outcome in prosthetic driven approach implant.